The first deep-sea mooring station in the eastern Levantine basin (DeepLev), outline and insights into regional sedimentological processes. (January 2020) - Katz, Timor; Weinstein, Yishai; Alkalay, Ronen; Biton, Eli; Toledo, Yaron; Lazar, Ayah; Zlatkin, Olga; Soffer, Rotem; Rahav, Eyal; Sisma-Ventura, Guy; Bar, Tslil; Ozer, Tal; et al.
Abstract: The eastern Levantine basin (ELB) is an ultra-oligotrophic, warm and saline marine system, significantly affected by climate change during the past several decades. The deployment of the first moored station at the ELB (DeepLev), at 1500 m water depth, 50 km offshore Haifa, Israel, aimed at enhancing synchronized measurements of physical and biogeochemical dynamics. The station carries an array of sediment traps and sensors that measure physical, chemical, and biological attributes along the water column. Here we describe the station and present sediment-flux data from the first 1.5 years of operation (since November 2016). We show that, despite DeepLev's offshore location and the open-sea characteristics of the water column, lateral transport from the continental margin contributes the greatest fraction of particulate flux to the seafloor at this site. This mostly occurs via intermediate nepheloid layer plumes entering the study area between depths of 180 and 800 m. Bottom currents are weak (average ± SD = 3.5 ± 2 cm s −1 ) and are unlikely to cause significant resuspension. Based on sedimentation rates obtained from nearby sediment cores and sediment particle fluxes sampled in the traps, calculated accumulation rates of total particulate matter and of particulate organic carbon at the seafloor were 95–108 g m −2 y −1 and 0.5–0.6 g m −2 y −1, respectively. Offshore changes in sedimentation rates and in surface sediment elemental ratios indicate that sediment originating from the continental margins is transported at least 100 km offshore.